Who benefits from benefits? Empirical research on tangible incentives - Andrea Hammermann; Alwine Mohnen (Institute for the Study of Labor (IZA), 2012)
Although a broad field of literature on incentive theory exists, employer-provided tangible goods (hereafter called benefits) have so far been neglected by economic research. A remarkable exception is an empirical study by Oyer (2008). In our study, we test some of his findings by drawing on a German data set. We use two waves of the GSOEP data (2006, 2008) to analyze the occurrence of benefits and their effects on employees' satisfaction. Our results provide evidence for economic as well as psychological explanations. Looking at differences in firms' and employees' characteristics we find that cost efficiency concerns, the purpose to signal good working conditions and the aim to ease employees' effort costs are evident reasons to provide benefits. Furthermore, analyzing the impact of tangible and monetary incentives on satisfaction and employees' feeling of being acknowledged by employers, we find different motivational effects. Our results support the psychological explanation that benefits are evaluated separately from other monetary wage components and are more likely to express employers' concern for their employees and recognition of their performance.
urn:nbn:de:101:1-201203145330
Keywords: C83; J32; M52; 330; nonmonetary incentives; benefits; work motivation; Leistungsanreiz; Arbeitsbedingungen; Leistungsmotivation; Deutschland